Students’ Metacognitive Process in Mathematical Problem Solving Based on Cognitive Style - Rina Apriyani; Ibrahim (Quadratic: Journal of Innovation and Technology in Mathematics and Mathematics Education, 2021)
This study is a qualitative literature review aimed to describe junior high school students’ metacognitive process in mathematical problem solving based on field independent and field dependent cognitive style. The research was done based on these following steps: 1) Data library relevant to variable and in accordance to the data source criteria was collected; 2) the data library was classified according to the grade and the subjects; 3) the data was analyzed. The instruments used in this study were the researchers and interview. The interview was conducted to confirm the classified data. Based e this study, it can be concluded that students using field independent style, competently can employ metacognitive process in planning, monitoring, and evaluating because they can write down the known fact and the question using mathematical symbol, choose the appropriate strategy, and answer the question thoroughly. Students using field dependent style were having difficulties in writing down the known fact and the question using mathematical symbol, choosing an appropriate strategy, and answering the question thoroughly.